Pengaruh Kompetensi dan Motivasi Kerja terhadap Kinerja Karyawan PT Indospec Asia - Marcel Putra Setiawan; Elmira Siska (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study discusses the influence of competence and work motivation on employee performance at PT Indospec Asia. The purpose of this study is to determine the extent to which competence and work motivation influence employee performance at PT Indospec Asia. The type of research used is quantitative research. Data were collected through distributing questionnaires to 113 respondents, namely employees of PT Indospec Asia. The data analysis technique used is multiple linear regression with the help of SPSS 25 software. The tests carried out were t-test (partial), F-test (simultaneous), and coefficient of determination (R2). The results of the analysis show that competence partially has a significant influence on employee performance as evidenced by the t count of 10.481 which is greater than the t table of 1.658 and the sig value of 0.000 is less than 0.5. Work motivation also has a partial influence on employee performance as evidenced by the t count of 2.710 which is greater than the t table of 1.658, the sig value of 0.008 is less than 0.5. Simultaneously, both variables have a significant influence with f count 140.381 greater than f table 3.08 and sig value 0.000 less than 0.5. The coefficient of determination (R2) value of 0.713 or 0.71 employee performance variables can be influenced by competence and work motivation.